2008
DOI: 10.1590/s1517-83822008000100024
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of glucoamylase from fungus Aspergillus awamori expressed in yeast Saccharomyces cerevisiae using different carbon sources

Abstract: Glucoamylase is widely used in the food industry to produce high glucose syrup, and also in fermentation processes for production beer and ethanol. In this work the productivity of the glucoamylase of Aspergillus awamori expressed by the yeast Saccharomyces cerevisiae, produced in submerged fermentation using different starches, was evaluated and characterized physico-chemically. The enzyme presented high specific activity, 13.8 U/mgprotein or 2.9 U/mgbiomass, after 48 h of fermentation using soluble starch as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 35 publications
2
22
0
1
Order By: Relevance
“…Glucoamylase activity increased from day 3 to day 5 and from day 11 to day 12, with maximum levels of glucoamylase activity obtained at day five (5) and day twelve (12) of submerged fermentation. Similar observations were reported by Fabiana et al [18], in their report; the maximum glucoamylase activity was achieved on day 3 of the submerged fermentation. Also, the decrease in glucoamylase production from day 6 to day 10 and from day 12 to day 14 could be attributed to high glucose concentration obtained by the microorganism, Christiane et al [19], in their research, reported that glucoamylase production by Aspergillus niger is repressed due to high glucose concentration in the microorganism, nevertheless, when glucose concentration decreases in the microorganism, the microorganism ( Aspergillus niger) then starts to produce glucoamylase again, to hydrolyze the substrate (in this case, amylopectin from guinea corn starch) to produce more glucose due to increased production of glucoamylase, as observed from the peaks obtained.…”
Section: Amylopectin Yieldsupporting
confidence: 91%
“…Glucoamylase activity increased from day 3 to day 5 and from day 11 to day 12, with maximum levels of glucoamylase activity obtained at day five (5) and day twelve (12) of submerged fermentation. Similar observations were reported by Fabiana et al [18], in their report; the maximum glucoamylase activity was achieved on day 3 of the submerged fermentation. Also, the decrease in glucoamylase production from day 6 to day 10 and from day 12 to day 14 could be attributed to high glucose concentration obtained by the microorganism, Christiane et al [19], in their research, reported that glucoamylase production by Aspergillus niger is repressed due to high glucose concentration in the microorganism, nevertheless, when glucose concentration decreases in the microorganism, the microorganism ( Aspergillus niger) then starts to produce glucoamylase again, to hydrolyze the substrate (in this case, amylopectin from guinea corn starch) to produce more glucose due to increased production of glucoamylase, as observed from the peaks obtained.…”
Section: Amylopectin Yieldsupporting
confidence: 91%
“…at pH varying between 5 and 6. In contrast [19] reported pH 3.5 and pH 4.0 to be the best for the production of α-amylase by B. amylolique faciens and A.…”
Section: -Effect Of Phmentioning
confidence: 86%
“…In lignocellulolytic waste there were traces of starch, on which amylase acted and produced glucose monomers. Glucoamylase consecutively hydrolyzes α-1,4 glycosidic bonds from non-reducing ends of starch, resulting in the production of glucose (Pavezzi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%